Credit Default Swaps and Firm Cyclicality - Norden, Lars; Yin, Chao; Zhao, Lei (Journal of Financial and Quantitative Analysis, 2025)
We find firm cyclicality decreases by 40% after the inception of credit default swap (CDS) trading. The effect stems from CDS firms’ less aggressive asset growth in good times and is stronger for firms facing a more severe empty creditor problem. Important identification issues are addressed. The result cannot be explained with debt overhang, bank lending cyclicality, or the cyclicality of firms’ business fundamentals. It holds for the cyclicality of various corporate outcomes (inventories, cash, and employment). Importantly, CDS trading impedes unhealthy growth and enhances profitability and firm value. Our finding indicates an important positive real effect of financial innovation.